PERAN STRATEGIS PEMERINTAH DESA PALLAKAWE DALAM MENINGKATKAN KESADARAN GENERASI Z TERHADAP BAHAYA NARKOBA - Devi Virnanda; Jihan Fahira; Moh Rian; Ananda Siti Nurbaiti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service activity aims to educate the younger generation in Pallakawe Village about the increasingly alarming dangers of drug abuse. Drug abuse is a serious problem that not only damages individual health but also affects the future of generations, social stability, and law and order. Generation Z, as a relatively young age group, is more vulnerable to the influence of drugs due to social factors, minimal legal understanding, and a lack of social control in the community. Through this outreach activity, the implementing team, consisting of students along with speakers from the police, delivered material on the negative impacts of drugs from a health, social, and legal perspective. The methods used included lectures, interactive discussions, and questions and answers, so that participants could understand the material more comprehensively. Participants in the outreach program showed high enthusiasm by asking questions and providing responses throughout the activity. The results of the activity showed that the community, especially the younger generation, gained better knowledge to avoid drug abuse. This activity is expected to grow collective awareness to protect themselves, their families, and their environment from the threat of drugs, while strengthening social resilience at the village level.